ANALISIS KUALITAS KERJA PEGAWAI TATA USAHA SEKOLAH MENENGAH ATAS NEGERI 1 BENGKULU TENGAH - Arisa Arisanti; Antonio Imanda; Harius Eko Saputra (UNIVED PRESS, Universitas Dehasen Bengkulu, 2020)
This study aims to find out the work quality of administrative Staff at SMAN 1of Central Bengkulu. This study uses a qualitative method. The data collection was donethrough observation, interview and documentation. The informants in this study amounted to 5 people, namely the headmaster, head of administration, teachers, administrative staff, and students. The results of this study show that the work quality of administrative staffat SMAN 1of Central Bengkulu is already good.Based on the interviews with the informants of administrative staff,the staff also have their own potential, optimal work results, work process and enthusiasm at work. Keywords: work quality, administration